REPOSISI DAN REAKTUALISASI PENDIDIKAN MADRASAH DALAM PEMBELAJARAN DI ERA DIGITAL - Tubagus Rahmat (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
There are two aspects to the development of education. First, education is based on the teachings of the religion because religious teachings considered to be civilized and human menadikan second, education based on information technology because it follows the development of the age in the digital age. Islamic education envisioned the Dharma human and productive because as has been expressed above that humans must Excel in idonesia SCIENCE and TECHNOLOGY based on IMTAQ. Humans are said to be productive when can follow science technology for an increased standard of living. With this Islamic education is considered as the alternative education in the face of the digital age. Islamic education certainly has a striking characteristic, namely education actualized by agam Islamic values. However, as the diselenggaran education by the State or other party necessarily secular in nature or worldliness. Therefore, Islamic education can serve as an innovation to respond to the demands of the present time. There are two things that menadi challenge Islamic education namely oprasional and managerial. Oprasional sure there is in the process of learning should reflect Islamic values by following the development of the times and a good managerial system of national education. Learning Islamic education tend to be considered less conventional pembelaaran will be adequate infrastructure because of the many education held madrasah originating from NGOs. In the challenge, education in madrasah apparently needs to improve the quality, especially in learning that should turn to non-conventional learning views that consider equivalent education in level.